2008
DOI: 10.1016/j.jcrs.2008.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Different epithelial cleavage planes produced by various epikeratomes in epithelial laser in situ keratomileusis

Abstract: Each epikeratome yielded reproducible but different cleavage planes of corneal epithelium. The results suggest that further study is needed to elucidate the wound-healing process after epi-LASIK because different cleavage planes produced by different epikeratomes may influence the process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In LASEK, the epithelial flap cleavage plane lies within the basement membrane between the lamina lucida and the lamina densa, but in epi-LASIK the cleavage plane may be under the basement membrane, depending on the device used. 8,69,95,96 Epithelial healing was similar between treatment groupsd4.2 days in LASEK and 4.9 days in epi-LASIK. 97 Hondur et al 76 also report similar UDVA results at all time points.…”
Section: Comparative Surface Ablation Studiesmentioning
confidence: 90%
“…In LASEK, the epithelial flap cleavage plane lies within the basement membrane between the lamina lucida and the lamina densa, but in epi-LASIK the cleavage plane may be under the basement membrane, depending on the device used. 8,69,95,96 Epithelial healing was similar between treatment groupsd4.2 days in LASEK and 4.9 days in epi-LASIK. 97 Hondur et al 76 also report similar UDVA results at all time points.…”
Section: Comparative Surface Ablation Studiesmentioning
confidence: 90%
“…Both epikeratomes successfully created epithelial flaps on more than 80% of the eyes in this study. However, Choi et al 43 reported that different cleavage planes of corneal epithelium may be created by different epikeratomes. It is still possible that the results reported here were partially influenced by the use of different epikeratomes.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we cannot exclude that this meta‐analysis results were also influenced by several parameters, which were different in the investigated studies. These parameters include the types of excimer lasers (with different laser beam shapes, ocular tracking systems and ablation profiles) and epikeratomes, and the application of intraoperative mitomycin C . We undertook a sensitivity analysis by dividing the studies into with and without mitomycin C groups and found that the mitomycin C seemed not to be a significant factor influencing the treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%